DEVELOPMENT AND CHARACTERIZATION OF BIO SOLUTION FOR OILY WASTEWATER TREATMENT - ABDUL RASHID, AMIERUL (2021)
The aim of this research is to develop an alternative treatment to the biological treatment to reduce COD and BOD levels in the oily wastewater. These are crucial aspect that necessary to be conducted, for instance, characterize the oily wastewater from industrial wastewater treatment plant (IWTP) and natural resources microorganism cocktail, and measure the removal efficiency of Chemical Oxygen Demand (COD), Bio-chemical Oxygen Demand (BOD), and Ammonia in the oily wastewater.